Estimation of evapotranspiration over the terrestrial ecosystems in China. Issue 1 (21st November 2012) - Li, Xianglan; Liang, Shunlin; Yuan, Wenping; Yu, Guirui; Cheng, Xiao; Chen, Yang; Zhao, Tianbao; Feng, Jinming; Ma, Zhuguo; Ma, Mingguo; Liu, Shaomin; Chen, Jiquan; et al.
ABSTRACT Quantifying regional evapotranspiration (ET) and environmental constraints are particularly important for understanding water and carbon cycles of terrestrial ecosystems. However, a large uncertainty in the regional estimation of ET still remains for the terrestrial ecosystems in China. This study used ET measurements of 34 eddy covariance sites within China and adjacent regions to examine the performance of the revised Remote Sensing‐Penman Monteith (RS‐PM) model over various ecosystem types including forests, grasslands, wetlands and croplands. No significant systematic error was found in the revised RS‐PM model predictions, which explained 61% of the ET variations at all of the validation sites. Regional patterns of ET at a spatial resolution of 10 × 10 km were quantified using a meteorology dataset from 753 meteorological stations, Modern Era Retrospective‐analysis for Research and Applications (MERRA) reanalysis products and satellite data such as the Advanced Very High Resolution Radiometer (AVHRR) leaf area index. ET decreased from the southeast of China toward the northwest. Relatively high ET values were found in the southern China such as Yunnan, Hainan, Fujian and Guangdong Provinces, whereas low ET values occurred in northwestern China such as in the Xinjiang autonomous region. On average, the annual ET presented an increasing trend during the 1982–2009, with relatively low ET in 1985, 1993, 1997, 2000 and 2009. We found that the mean annual ET was higher than world average, ranging spatially between 484 and 521 mm yr−1, with a mean value of 500 mm yr−1, which accounted for approximately 5·6–8·3% of the world's total land‐surface ET. Copyright © 2012 John Wiley & Sons, Ltd.